A new fish species of the subfamily Serraninae (Perciformes, Serranidae) from the Philippines - Williams, Jeffrey T.; Carpenter, Kent E. (Zootaxa, 2015)
A new species of serranine fish is described from the Philippine Islands. A single specimen of a new species, Chelidoperca santosi, captured by fishermen working in Palawan waters was discovered in the public fish market in Iloilo City, Panay, Philippines. Two additional specimens of the new species, also from the Philippines, were subsequently discovered in the collections of the Museum Victoria, Australia. The new species is currently known only from the Philippines and is characterized by its distinctive coloration with a row of four small dark spots on the snout (two in front of each eye) and two dark spots on the chin (one on each side of the symphysis of the dentaries), a white anal fin with six large yellow spots separated by broad white interspaces and a narrow yellow distal border, caudal fin with narrow yellow bars and a yellowish distal margin and no dark spots, and a combination of meristic and morphological characters.